2016
DOI: 10.3389/fnins.2016.00447
|View full text |Cite
|
Sign up to set email alerts
|

Music Proficiency and Quantification of Absolute Pitch: A Large-Scale Study among Brazilian Musicians

Abstract: Absolute pitch (AP) is the ability to identify and name the pitch of a sound without external reference. Often, accuracy and speed at naming isolated musical pitches are correlated with demographic, biological, and acoustical parameters to gain insight into the genesis and evolution of this ability in specific cohorts. However, the majority of those studies were conducted in North America, Europe, or Asia. To fill this gap, here we investigated the pitch-naming performance in a large population of Brazilian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…However, there is diversity of opinion about what level is required. For example, Takeuchi and Hulse (1993) cite a series of studies with mean accuracy levels spanning from 58% to 99%, while Leite, Mota-Rolim and Queiroz (2016) argue for a threshold of 20% accuracy on the basis of error probability. With no fixed method to test AP, the required accuracy rate is additionally influenced by differences in measurement tools and criteria (Bermudez & Zatorre, 2009a).…”
Section: Definition and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…However, there is diversity of opinion about what level is required. For example, Takeuchi and Hulse (1993) cite a series of studies with mean accuracy levels spanning from 58% to 99%, while Leite, Mota-Rolim and Queiroz (2016) argue for a threshold of 20% accuracy on the basis of error probability. With no fixed method to test AP, the required accuracy rate is additionally influenced by differences in measurement tools and criteria (Bermudez & Zatorre, 2009a).…”
Section: Definition and Prevalencementioning
confidence: 99%
“…Greater evidenced consensus is being achieved on the prevalence of AP in musician subgroups, with cross-cultural studies enriching the consideration of the potential for population differences based on factors including genetic, ethnic and/or language backgrounds. For example, amongst music school students in Brazil, Leite et al (2016) found that 4% achieved 85% accuracy on a test of tone identification, with 18% achieving accuracy significantly above the level of chance. Comparing Japanese and Polish music students and applying an 80% accuracy threshold, Miyazaki et al (2012) identified a 49% prevalence in the former group and 12% in the latter.…”
Section: Definition and Prevalencementioning
confidence: 99%
“…While most studies of absolute pitch have concentrated on individuals with near-perfect accuracy in pitch labeling, other research has suggested that many musicians have pitchlabeling abilities somewhere in the middle of a continuum of pitch identification accuracies (Levitin and Rogers, 2005;Wilson et al, 2009;Wengenroth et al, 2014;Leite et al, 2016). This intermediate ability has been called "quasi-absolute pitch, " and while exact definitions vary, generally refers to accuracy above chance but below around 85%.…”
Section: Introductionmentioning
confidence: 99%
“…Consider three subgroups of people with varying levels of global AP: the first scores at chance level across timbres (“non-AP”), another subgroup scores above chance but below ~85% across timbres (“quasi-AP”), and yet another subgroup scores above ~85% across timbres (“AP”). (For discussion of “quasi” or “partial” AP, see [ 13 14 ]). Members of each of these subgroups could have an added advantage for the timbre of one or more of their main instruments, and this added advantage is what we would refer to as “ISAP”—for quasi-AP or AP possessors, ISAP is thus an instrument-specific gain in absolute pitch ability.…”
Section: Introductionmentioning
confidence: 99%